Receipt of information about diet by pregnant women: A cross-sectional study. Issue 6 (December 2019) - Bryant, Jamie; Waller, Amy E.; Cameron, Emilie C.; Sanson-Fisher, Rob W.; Hure, Alexis J.
Abstract: Problem: Given the influence of diet on infant and maternal health outcomes, adequate knowledge about nutrition during pregnancy is critical. Aims: To examine among women receiving antenatal care the proportion who: (1) believe information about diet should be provided as part of routine antenatal care; (2) recall receiving advice about diet as part of care including: (a) when information was provided, (b) the healthcare provider who gave information, and (c) the format in which it was provided; and (3) attitudes towards information received. Methods: A cross-sectional survey was conducted with women attending a public antenatal clinic in New South Wales, Australia. Women were eligible to participate if they were: pregnant or had given birth in the previous 10 weeks; ≥ 18 years; and had at least one prior antenatal appointment for their current pregnancy. Findings: A total of 223 women (64% consent rate) participated. While the majority (86%) believed healthcare providers should be giving dietary information to pregnant women, only 63% recalled receiving information during their current pregnancy. Most often it was given by a midwife (76%). Information was initially provided in the first (52%) or second (38%) trimester, in both written and verbal form (60%). Approximately one third of participants felt overwhelmed or confused by which foods should be avoided during pregnancy. Conclusions: A third of women did not recall receiving advice about diet as part of routine antenatal care. There is a need to develop a pathway to provide women with reliable, comprehensive advice about diet early in pregnancy.